ADVANTAGES OF USING IMAGE MEDIA FROM LEATHER PUPPETS AND MASKS TO IMPROVE SPEECH SKILLS - Sukapdi Sukapdi (Universitas Muhammadiyah Purwokerto, 2023)
This study analyzes the difficulty in an effort to improve English speaking skills for students at the Institut Teknologi Nasional Yogyakarta (ITNY) by using visual aids with leather puppets materials and masks. Materials used for visual aids was obtained from the Wukirsari Hamlet, Imogiri District, Bantul Regency, Yogyakarta. The result shows that the ability to improve learning of English subjects can strongly  improve the speaking skills of ITNY students, especially (1) mastering vocabulary, (2) mastering grammar, and (3) mastering ideas to improve speaking skills. In addition, the advantage of using visual media is that it can motivate students to improve their speaking skills and provide guidance and constructive ideas. This can be seen from the average scores on the competency tests. In the first cycle it was 72.7 with a learning completion (LC) of 11.4%, in the second cycle it was 75.9 with a 68.6% increase in LC, and 79.2 with a 91.4% increase in LC in the third cycle.